Pengaruh Utang Luar Negeri Dan Penanaman Modal asing (PMA) Terhadap Pertumbuhan Ekonomi Di Indonesia - Saharuddin Didu (Jurnal Ekonomi-Qu, 2017)
This research aimed to determine the effect of foreign debt and foreign direct investment on economic growth in indonesia both partially and simultaneously. This research uses multiple regression analysis, using the computer program SPSS version 16.0Results of this research showed that apparently foreign debt and foreign investment has positive and significant effect on economic growth. Regression results obtained from the value of R Square of  0.76 this illustrates that the independent variabels in this study were able to give an explanation of the dependent variable was 76.0% the 24.0%  more influenced by other variables outside research as ekspor – impor, kurs and PMDN.